The economic burden of cardiovascular disease and hypertension in low- and middle-income countries: a systematic review - Adrian Gheorghe; Ulla Griffiths; Adrianna Murphy; Helena Legido-Quigley; Peter Lamptey; Pablo Perel (BMC, 2018)
Abstract Background The evidence on the economic burden of cardiovascular disease (CVD) in low- and middle- income countries (LMICs) remains scarce. We conducted a comprehensive systematic review to establish the magnitude and knowledge gaps in relation to the economic burden of CVD and hypertension on households, health systems and the society. Methods We included studies using primary or secondary data to produce original economic estimates of the impact of CVD. We searched sixteen electronic databases from 1990 onwards without language restrictions. We appraised the quality of included studies using a seven-question assessment tool. Results Eighty-three studies met the inclusion criteria, most of which were single centre retrospective cost studies conducted in secondary care settings. Studies in China, Brazil, India and Mexico contributed together 50% of the total number of economic estimates identified. The quality of the included studies was generally low. Reporting transparency, particularly for cost data sources and results, was poor. The costs per episode for hypertension and generic CVD were fairly homogeneous across studies; ranging between $500 and $1500. In contrast, for coronary heart disease (CHD) and stroke cost estimates were generally higher and more heterogeneous, with several estimates in excess of $5000 per episode. The economic perspective and scope of the study appeared to impact cost estimates for hypertension and generic CVD considerably less than estimates for stroke and CHD. Most studies reported monthly costs for hypertension treatment around $22. Average monthly treatment costs for stroke and CHD ranged between $300 and $1000, however variability across estimates was high. In most LMICs both the annual cost of care and the cost of an acute episode exceed many times the total health expenditure per capita. Conclusions The existing evidence on the economic burden of CVD in LMICs does not appear aligned with policy priorities in terms of research volume, pathologies studied and methodological quality. Not only is more economic research needed to fill the existing gaps, but research quality needs to be drastically improved. More broadly, national-level studies with appropriate sample sizes and adequate incorporation of indirect costs need to replace small-scale, institutional, retrospective cost studies.